Znaki pamięci. O komemoratywnym charakterze obrazka religijnego - Jarkiewicz, Katarzyna (Archiwa, Biblioteki i Muzea Kościelne, 2017)
Shaped in the fifteenth century religious images in Baroque took commemorative figure corresponding to the specifics of Catholic funeral rites. It became a symbol of mourning leaflets imparting basic knowledge of deceased persons and inspiring prayers and memorial services. Mourners in the sense of religious obligation hid the souvenirs in the prayer books and drawers, pinned to the memory array or presented in other places. This process strengthened the experience of world wars that shaped the need to honor the soldiers’ images. Secular heroes thus replaced Christ and the saints. Culture memory strengthened and included on the pictures secular content. Disappears need to care for the salvation of the living dead for mentioning them as relevant to our identity as people. This process intensifies the penetration of virtual reality memorabilia and development of the funeral culture.